Quackery in the Netherlands Art of Late 15th — First Half of the 16th Century: Classical Allusions in the Renaissance Iconography of Deceit - Kovbasiuk, Stefaniia A. (Actual Problems of Theory and History of Art, 2015)
The author of the article aspires to explore specific ways of depiction of quackery that is explicitly traceable in the art of the Renaissance Netherlands. Among the most popular depictions of quacksalvers the leading position undoubtedly belongs to the “surgeon-quack”. His iconography was inspired by both narrative sources and the real practice of quacks in the 16th century. Painters amplified it with different symbols of Folly: “stone of folly” on a patient’s forehead, a turned upside-down funnel on a quack’s head, broken eggs, where “a fool sits”, a fool’s sash of “Frau Hexe” etc. In addition to surgeon-quack there existed another image of quacksalver — the one of “tooth-puller”. This topos was not limited to moralizing effects: it is likely enough that this kind of imagery was used for the purposes of religious rhetoric as well. Tradition of Classical antiquity coupled with Humanistic one, in combination with the Netherlands’ popular culture resulted in creation of a versatile image of quack. He was depicted as a trickster worth of gallows, a fool who overestimates his medical training, and at the same time — a jester who mocks vices and folly of the society.
Keywords: quackery; deceit; folly; antiquit; H. Bosch